2020
DOI: 10.26434/chemrxiv.12730793.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Limiting Electrospray Deposition on Polymer Templates

Abstract: <p>Electrospray deposition (ESD) applies a high voltage to liquids flowing through narrow capillaries to produce monodisperse generations of droplets down to hundreds of nanometers in diameter, each carrying a small amount of the delivered solute. This deposition method has been combined with insulated stencil masks for fabricating micropatterns by spraying solutions containing nanoparticles, polymers, or biomaterials. To optimize the fabrication process for micro-coatings, a self-limiting electrospray d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Both of these effects are consistent with our past results with SU-8 possessing higher dielectric constant, but more facile solvent swelling and low glass transition due to the oligomeric nature of the substance. 20 It is interesting to note that the addition of either miscible or immiscible components does appear to stabilize the thickness of the SU-8, which is suggestive that additives offset this sensitivity to solvent.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Both of these effects are consistent with our past results with SU-8 possessing higher dielectric constant, but more facile solvent swelling and low glass transition due to the oligomeric nature of the substance. 20 It is interesting to note that the addition of either miscible or immiscible components does appear to stabilize the thickness of the SU-8, which is suggestive that additives offset this sensitivity to solvent.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously observed that, while SU-8 is sensitive to solvent, its higher dielectric strength leads to it being more self-limiting as a mask material. 20 Taken together with the fact that blending seems to stabilize SU-8 sprays to solvent effects, it follows that adding PS to SU-8 would improve the stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect makes it difficult to build thick, continuous layers on insulators. To address this issue, we utilize a dielectric stencil to focus material to the underlying target substrate [19]- [21]. The stencil is a carefully selected material with a custom orifice that is placed on top of the target, as shown in Fig.…”
Section: "Stenciling" Through a Dielectric Constant Mismatchmentioning
confidence: 99%
“…In addition, the spray of insulating polymers produces thicknesslimited films in which the charge accumulation repels incoming spray droplets. 4,11,12 This self-limiting behavior enables the conformal coating of complex 3D surfaces. 13 Recent work from our group has shown that methylcellulose (MC) forms a selflimiting coating with a unique nanowire architecture when processed by ESD from water : ethanol solutions.…”
Section: Introductionmentioning
confidence: 99%